The Lasting Legacy of Seasonal Influenza: In-Utero Exposure and Labor Market Outcomes - Hannes Schwandt (Institute of Labor Economics (IZA), 2017)
Pregnancy conditions have been shown to matter for later economic success, but many threats to fetal development that have been identified are difficult to prevent. In this paper I study seasonal influenza, a preventable illness that comes around every year and causes strong inflammatory responses in pregnant women. Using administrative data from Denmark, I identify the effects of maternal influenza on the exposed offspring via sibling comparison, exploiting both society-wide influenza spread and information on individual mothers who suffer strong infections during pregnancy. In the short term, maternal influenza leads to a doubling of prematurity and low birth weight, by triggering premature labor among women infected in the third trimester. Following exposed offspring into young adulthood, I observe a 9% earnings reduction and a 35% increase in welfare dependence. These long-term effects are strongest for influenza infections during the second trimester and they are partly explained by a decline in educational attainment, pointing to cognitive impairment. This effect pattern suggests that maternal influenza damages the fetus through multiple mechanisms, and much of the damage may not be visible at birth. Taken together, these results provide evidence that strong infections during pregnancy are an often overlooked prenatal threat with long-term consequences.
Keywords: I10; J24; J3; J13; 330; pregnancy conditions; seasonal influenza; labor market outcomes